2013
DOI: 10.1126/science.1231357
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Error Governs Pharmacologically Induced Amnesia for Learned Fear

Abstract: Although reconsolidation opens up new avenues to erase excessive fear memory, subtle boundary conditions put constraints on retrieval-induced plasticity. Reconsolidation may only take place when memory reactivation involves an experience that engages new learning (prediction error). Thus far, it has not been possible to determine the optimal degree of novelty required for destabilizing the memory. The occurrence of prediction error could only be inferred from the observation of a reconsolidation process itself… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
352
9
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(383 citation statements)
references
References 16 publications
21
352
9
1
Order By: Relevance
“…This is in line with recent suggestions that the period of time of maximum US expectancy (i.e., fear) is a key factor to improve therapeutic strategies such as enhancing inhibitory learning based on an expectancy violation model (Craske et al 2014). In addition, this is also in agreement with reports in humans (Sevenster et al 2013(Sevenster et al , 2014 which strongly indicate that post-retrieval changes in US-expectancy can be used to reveal the different processes triggered by nonreinforced memory reactivation.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is in line with recent suggestions that the period of time of maximum US expectancy (i.e., fear) is a key factor to improve therapeutic strategies such as enhancing inhibitory learning based on an expectancy violation model (Craske et al 2014). In addition, this is also in agreement with reports in humans (Sevenster et al 2013(Sevenster et al , 2014 which strongly indicate that post-retrieval changes in US-expectancy can be used to reveal the different processes triggered by nonreinforced memory reactivation.…”
Section: Discussionsupporting
confidence: 80%
“…This implies that memory reactivation will lead to memory destabilization if, and only if, a prediction error is experienced by the animal. This hypothesis has recently found support both in humans and rats through two manipulations that induce an error prediction during memory reactivation: (a) varying the amount of CS or response exposure (Exton-McGuinness et al 2014bReichelt et al 2012Reichelt et al , 2013Sevenster et al 2012Sevenster et al , 2013Sevenster et al , 2014, and (b) varying the temporal expectation of the US presentation (Diaz-Mataix et al 2013). …”
mentioning
confidence: 99%
“…Indeed, not all memories become labile when reactivated; boundary conditions, including the strength of initial memory encoding and the age of the memory at the time of retrieval, determine the likelihood of destabilization upon reactivation (Milekic and Alberini 2002;Eisenberg and Dudai 2004;Suzuki et al 2004;Winters et al 2009). These boundary conditions may be related to the putative role of reconsolidation in memory updating (Sara 2000;Rodriguez-Ortiz et al 2005;Morris et al 2006;Hupbach et al 2007;Rossato et al 2007;Lee 2009;Forcato et al 2010;Sevenster et al 2013). Accordingly, stronger or more remote memories may be less likely to be altered in the absence of salient novel information (Lee 2009;Winters et al 2009).…”
mentioning
confidence: 99%
“…It is a process that is suggested to be conditional on a number of boundary conditions, such as the context in which reactivation takes place (Hupbach et al, 2008), the original memoryā€™s age and strength (Wichert et al, 2011), or whether something new is learned after reactivation (i.e. prediction error; Sevenster et al, 2012, 2013). The increasing number of boundary conditions raises the question whether other yet to be empirically uncovered boundary conditions may have dampened finding indisputable reconsolidation effects in this study.…”
Section: Discussionmentioning
confidence: 99%
“…One line of research remained close to the animal studies and demonstrated experimentally that human memories can be changed via pharmacological manipulations (e.g. Brunet et al, 2008; Kindt, Soeter, & Vervliet, 2009; Sevenster, Beckers, & Kindt, 2012, 2013; Soeter & Kindt, 2012), while the other line showed that memories can be altered with behavioural manipulations (e.g. Forcato et al, 2007; Hupbach, Gomez, Hardt, & Nadel, 2007; James et al, 2015; Schwabe & Wolf, 2009; Schiller et al, 2010; Wichert, Wolf, & Schwabe, 2011; 2013a, 2013b; see also van den Hout & Engelhard, 2012).…”
mentioning
confidence: 99%